Fetal Heart Rate Patterns in Labor and the Risk of Neonatal Encephalopathy: A Case Control Study. Issue 12 (December 2022) - Reynolds, Adam J.; Murray, Michelle L.; Geary, Michael P.; Ater, Stewart B.; Hayes, Breda C.
Abstract : (Abstracted from Eur J Obstet Gynecol Reprod Biol 2022;273:69–74) The main method of fetal monitoring in labor today is cardiotocography (CTG). When it was introduced in the 1960s, it was thought that CTG could detect fetal heart rate (FHR) patterns that indicated hypoxia and ultimately prevent hypoxic brain injury.